A cross sectional study amongst paramedical workers and nursing students regarding awareness of various aspects of biomedical waste (management and handling) rules - Acharya, Rekha; Sharma, Gaurav; Sethia, Renu; Meena, Rattiram (International Journal Of Community Medicine And Public Health, 2017)
Background: Various type of waste are produced during healthcare activities. Such waste generated has more chances of causing serious infection and also injury to persons coming in contact with them directly or indirectly. Lack of adequate and appropriate knowledge of handling of healthcare waste may lead to serious health consequences to such persons and have significant adverse impact on the environment as well. The objective of the study was to assess the level of Awareness of various aspects of Biomedical Waste (Management and handling) Rules amongst paramedical workers and nursing students. Methods:This was a cross-sectional study. The study was conducted amongst paramedical workers and nursing students posted at Prince Bijay Singh Memorial (PBM) and Associated Group of Hospitals Attached to Sardar Patel Medical College, Bikaner. Results: Out of 607 respondents, maximum (57%) were Paramedical workers followed by General Nursing and Midwifery (G. N. M) students (24.7%), and B.Sc. nursing students (18.3%). Majority (70.6%) of the participants didn’t have any training on Biomedical Waste management. 20.6% of study population had poor awareness regarding various aspects of Biomedical Waste Management. Highly significant difference was seen when awareness of various professional group regarding different aspects of Biomedical Waste Management was compared. Conclusions:The lack of proper and complete awareness about Biomedical Waste Handling and management rules impacts practice of appropriate waste disposal leading to serious health consequences, thus there is need to reinforce and update knowledge of health care workers on the subject.